Spatio-temporal characteristics of hazardous weather affecting Chinese airports based on the ERA5/ERA5-land reanalysis dataset - Lei, Ting; Jin, Chenxi; Qi, Chen (Frontiers in Climate, 2022)
The growing demand for air transportation has led to increased air traffic and airline operations at airports worldwide, while hazardous weather conditions have a considerable impact on the efficiency and safety of air traffic. The long-term and high-resolution state-of-art fifth-generation reanalysis of the European Center for Medium-Range Weather Forecasts (ECMWF) (ERA5) and ERA5-land provide us a perspective on the climatological characteristics of hazardous weather conditions affecting Chinese airports. These hazardous weather conditions include low-level wind shear (LLWS), limited visibility (LIMV), thunderstorms (TSTMs), and snowfall (SNOW). The LLWS is frequent in winter but rare in summer. At the airports in the north of eastern China, managers should take more precautions about LLWS from February to March and October to November. LIMV is major hazardous weather in the south of eastern China that should be carefully monitored in winter, especially from December to January. In northwestern China, LIMV is rare, especially at Yinchuan and Lanzhou airports. TSTMs frequently occur in South China and Southwest China, especially in Yunnan, Guangxi, Guangdong, and eastern Tibet. The corresponding active period is summer. SNOW frequently occurs over the Tibet Plateau and parts of Xinjiang province. SNOW is generally active in early winter (December–January) at Urumchi airport but at Lhasa airport in late winter (February–March). There is no SNOW throughout the year in the south of eastern China. The observations also verify such characteristics of the annual cycles of the four hazardous weather conditions. The trend analysis does not express many warnings on hazardous weather conditions except the SNOW. The SNOW at Lhasa airport shows an increasing trend. Considering the frequent SNOW in Lhasa, more attention should be put to monitoring this weather here.